1993
DOI: 10.1046/j.1468-2982.1993.1305343.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-1 Beta is Increased in Cluster Headache

Abstract: We measured serum interleukin-1 beta (IL-1 beta) in 24 episodic cluster headache (CH) patients and 45 normal controls using a specific ELISA method. There was an increase in IL-1 beta in all CH patients compared to controls. IL-1 beta was further increased during the ictal phase of CH compared to patients between attacks and normal individuals. Between attacks, IL-1 beta was also significantly increased compared to controls. We suggest that these results represent an activation of the immune system in CH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 17 publications
3
43
0
2
Order By: Relevance
“…The immunoinflammatory system takes part in modulating the mechanisms giving rise to migraine, possibly by the intermediation of cytokines that are broadly expressed by several cells Review Lovati, D'Amico, Raimondi, Mariani & Bertora of the CNS, including the neurons that are considered to mediate pain in neurovascular inflammation [55]. Activation of the immune system has been identified in CH in which an increase in IL-1 b, in particular during the ictal phase, can be found [56].…”
Section: Cytokinesmentioning
confidence: 99%
“…The immunoinflammatory system takes part in modulating the mechanisms giving rise to migraine, possibly by the intermediation of cytokines that are broadly expressed by several cells Review Lovati, D'Amico, Raimondi, Mariani & Bertora of the CNS, including the neurons that are considered to mediate pain in neurovascular inflammation [55]. Activation of the immune system has been identified in CH in which an increase in IL-1 b, in particular during the ictal phase, can be found [56].…”
Section: Cytokinesmentioning
confidence: 99%
“…Furthermore, recombinant IL-2 and interferon-β were found to counteract this peripheral downregulation 47–49. In a later work, Martelletti et al observed that the serum IL-1β level was significantly higher in ECH patients compared to HCs, intraictally as well as postictally 50. In addition, intraictal concentrations were higher than postictal values.…”
Section: Moa Of Cervical Vns In Cluster Headache (Human and Preclinicmentioning
confidence: 91%
“…Orbital phlebography [20] and gallium single photon emission computerized tomography scans [21] have suggested inflammation in the cavernous sinus ipsilateral to CH pain during cluster periods. Inflammatory mediators can be detected in cerebrospinal fluid [22] and blood (eg, interleukin-1β) [23] during CH periods and CH attacks and an increase in some restricted subsets of circulating leukocytes (eg, Leu7+, LeuM3+) has been detected specifically during CH attacks [24]. Other evidence for a dysimmune process in CH comes from genotyping of major histocompatibility complex genes.…”
Section: Pathophysiologic Rationale For the Therapeutic Efficacy Of Cmentioning
confidence: 99%